PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI SEKOLAH DASAR - SARI, MEGA MARANTIKA (Universitas Negeri Padang, 2014)
ABSTRACT The purpose of this research was to describe the improvement of the students’ learning achievement in Natural Science by using experimental method in grade IV of SDN 08 Tarok Dipo Kota Bukittinggi. This was a Classroom Action Research which applied either equalitative or quantitative approach. The subject of the research was the practitioner teacher and 25 students in grade IV of SDN 08 Tarok Dipo Kota Bukittinggi. The research finding showed that the students’ learning achievement in Natural Science improved from 68% (adequate) to 92% (very good). Hence, the use of experimental method could increase the students’ learning achievement in Natural Science in grade IV of SDN 08 Tarok Dipo Kota Bukittinggi. Kata Kunci: IPA; metode eksperimen; SD